Sustainable Use of Plant Resources of Kurseong Hills, Darjeeling District - Mallick, Rwitabrata; Sanyal, Pranabes (Indian Forester, 2012)
Plant resources are naturally occurring substances that are considered valuable in their relatively unmodified (natural) form. The value of such resources rest in the amount of the material available and the demand for it. Both extraction of the basic resource and refining it into a purer, directly usable form are generally considered natural-resource activities, even though the latter may not necessarily occur near the former. Conservation and sustainable use of plant resources means an occurrence of improvement by virtue of preventing loss or injury and careful management of the plant resources. The management process includes optimum utilization of natural resources in a scientific manner for the betterment of man and environment and for sustainable development.